Atomic sizes from atomic interactions - Ganguly, Parthasarathy (Journal of Molecular Structure, 2009)
We obtain an atomic size, r(nZ)(c), in the presence of an interaction (represented by an electron-hole pair, e(-)h(+) as in vacuum polarization techniques) as a sum of contribution, r(nv), from the interaction of n(val) valence sand p-electrons and a contribution r(RG) from inner filled shell electrons with rare-gas configuration. The method is applicable to all elements for a given electron configuration that is usually available simply from the position of the elements in the periodic table. The sizes thus obtained are close to other ``core sizes'' obtained in the literature. The transition metal elements are treated as group II elements. This method gives sizes for the actinide and trans-actinide elements without requiring relativistic corrections. The importance of these sizes in interpreting interatomic distances in terms of electronic configuration is illustrated for actinide elements. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Atomic size; Ionic radii; Vacuum polarization